A Clash between the Business and Political Climates in Sweden – Gender in the European Structural Fund Partnerships - Hedfeldt, Mona; Hedlund, Gun (European Spatial Research and Policy, 2011)
In this paper we highlight and discuss a Swedish equality paradox in two different spheres: entrepreneurship and politics. We focus on the EU Structural Funds and women entrepreneurs’ access to resources through the European Regional Development Fund (ERDF). Combining human geography and political science, we draw upon network and partnership theory posing questions concerning the room for manoeuvre for women entrepreneurs to gain access to relevant networks, to create new networks in order to establish relations with EU related partnerships, and to gain access to the process of allocating EU structural fund financial resources.